2020
DOI: 10.3138/jcfs.51.3-4.004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 Confinement on the Spanish Family: Adaptation or Change?

Abstract: Spain is one of the countries that has been most affected by the COVID-19 pandemic worldwide. As a southern European country, Spain is characterized by high levels of sociability and the vital role of the family in its social structure. The intense confinement phase raised many questions about how the Spanish family would adapt to this crisis. This study analyzes the consequences of confinement on three areas of family life: the emotional state of its members, family relationships inside and outside the home, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 14 publications
4
31
0
4
Order By: Relevance
“…Moreover, German national panel data collected between May 2020 and June 2020 (n.b., a timeline encompassed by the present study) suggests a modest increase in satisfaction with family life over this time span (Huebener et al, 2020). Similar results, suggesting the maintenance of satisfaction with family life during the pandemic lockdown, were likewise found in a nationally representative study conducted in Spain (Ayuso et al, 2020).…”
Section: Trajectories In Family Demands and Satisfaction With Family Lifesupporting
confidence: 88%
“…Moreover, German national panel data collected between May 2020 and June 2020 (n.b., a timeline encompassed by the present study) suggests a modest increase in satisfaction with family life over this time span (Huebener et al, 2020). Similar results, suggesting the maintenance of satisfaction with family life during the pandemic lockdown, were likewise found in a nationally representative study conducted in Spain (Ayuso et al, 2020).…”
Section: Trajectories In Family Demands and Satisfaction With Family Lifesupporting
confidence: 88%
“…Moreover, German national panel data collected between May 2020 and June 2020 (n.b., a timeline encompassed by the present study) suggests a modest increase in satisfaction with family life over this time span (Huebener et al, 2020). Similar results, suggesting the maintenance of satisfaction with family life during the pandemic lockdown, were likewise found in a nationally representative study conducted in Spain (Ayuso et al, 2020).…”
Section: Trajectories In Family Demands and Satisfaction With Family Lifesupporting
confidence: 84%
“…The most frequently mentioned positive effects expected from the transition to remote learning were the saving of time as well as flexibility issues regarding time and work management, the (asynchronous) reception and processing of course materials, choice of learning locations, and in general. These advantages of remote learning had already been highlighted previously (Daymont et al, 2011), but during the current pandemic, these benefits seem particularly important for adequately addressing and compensating challenges in other areas of life, such as those associated with job loss (Aucejo et al, 2020) and new obligations in family life (Ayuso et al, 2020). Hence, universities and lecturers should try to maximize flexibility options during this challenging time.…”
Section: Central Findings and Implicationsmentioning
confidence: 86%
“…Indeed, research shows that the pandemic has led to anxiety, distress, and uncertainty among German adults in general (Benke et al, 2020 ; Petzold et al, 2020 ). International studies revealed that the pandemic has had several negative impacts on students' well-being and psychosocial variables (Cao et al, 2020 ; Wang and Zhao, 2020 ), and that it has led to job losses or reduced income (Aucejo et al, 2020 ) as well as to new obligations and challenges in family life (Ayuso et al, 2020 ). However, remote teaching and learning can also have positive effects for students, for example, increased flexibility regarding the time and place of learning (Arkorful and Abaidoo, 2015 ).…”
Section: Introductionmentioning
confidence: 99%